Biochemical, pathological and ultrastructural investigation of whether lamotrigine has neuroprotective efficacy against spinal cord ischemia reperfusion injury. Issue 10 (October 2021) - Kahveci, Fatih Ozan; Kahveci, Ramazan; Gokce, Emre Cemal; Gokce, Aysun; Kısa, Üçler; Sargon, Mustafa Fevzi; Fesli, Ramazan; Sarı, Muhammed Fatih; Gürer, Bora
Highlights: Lamotrigine administration has shown neuroprotective effects against spinal cord ischemia reperfusion injury. Neuroprotective effects of lamotrigine seem to be related its membrane stabilizing, antioxidative and antiinflammatory effects. Neuroprotective effects of lamotrigine further proved by ultrastructural and behavioral analysis. Abstract: Introduction: Lamotrigine, an anticonvulsant drug with inhibition properties of multi-ion channels, has been shown to be able to attenuates secondary neuronal damage by influencing different pathways. The aim of this study was to look into whether lamotrigine treatment could protect the spinal cord from experimental spinal cord ischemia-reperfusion injury. Materials and methods: Thirty-two rats, eight rats per group, were randomly assigned to the sham group in which only laparotomy was performed, and to the ischemia, methylprednisolone and lamotrigine groups, where the infrarenal aorta was clamped for thirty minutes to induce spinal cord ischemia-reperfusion injury. Tissue samples belonging to spinal cords were harvested from sacrificed animals twenty-four hours after reperfusion. Tumor necrosis factor-alpha levels, interleukin-1 beta levels, nitric oxide levels, superoxide dismutase activity, catalase activity, glutathione peroxidase activity, malondialdehyde levels and caspase-3 activity were studied. Light and electron microscopic evaluations were also performed to reveal the pathological alterations. Basso, Beattie, and Bresnahan locomotor scale and the inclined-plane test was used to evaluate neurofunctional status at the beginning of the study and just before the animals were sacrificed. Results: Lamotrigine treatment provided significant improvement in the neurofunctional status by preventing the increase in cytokine expression, increased lipid peroxidation and oxidative stress, depletion of antioxidant enzymes activity and increased apoptosis, all of which contributing to spinal cord damage through different paths after ischemia reperfusion injury. Furthermore, lamotrigine treatment has shown improved results concerning the histopathological and ultrastructural scores and the functional tests. Conclusion: These results proposed that lamotrigine may be a useful therapeutic agent to prevent the neuronal damage developing after spinal cord ischemia-reperfusion injury.